More than one way to smell ashore – Evolution of the olfactory pathway in terrestrial malacostracan crustaceans - Krieger, Jakob (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2021)
Crustaceans provide a fascinating opportunity for studying adaptations to a terrestrial lifestyle because within this group, the conquest of land has occurred at least ten times convergently. The evolutionary transition from water to land demands various morphological and physiological adaptations of tissues and organs including the sensory and nervous system. In this review, we aim to compare the brain architecture between selected terrestrial and closely related marine representatives of the crustacean taxa Amphipoda, Isopoda, Brachyura, and Anomala with an emphasis on the elements of the olfactory pathway including receptor molecules. Our comparison of neuroanatomical structures between terrestrial members and their close aquatic relatives suggests that during the convergent evolution of terrestrial life-styles, the elements of the olfactory pathway were subject to different morphological transformations. In terrestrial anomalans (Coenobitidae), the elements of the primary olfactory pathway (antennules and olfactory lobes) are in general considerably enlarged whereas they are smaller in terrestrial brachyurans compared to their aquatic relatives. Studies on the repertoire of receptor molecules in Coenobitidae do not point to specific terrestrial adaptations but suggest that perireceptor events – processes in the receptor environment before the stimuli bind – may play an important role for aerial olfaction in this group. In terrestrial members of amphipods (Amphipoda: Talitridae) as well as of isopods (Isopoda: Oniscidea), however, the antennules and olfactory sensilla (aesthetascs) are largely reduced and miniaturized. Consequently, their primary olfactory processing centers are suggested to have been lost during the evolution of a life on land. Nevertheless, in terrestrial Peracarida, the (second) antennae as well as their associated tritocerebral processing structures are presumed to compensate for this loss or rather considerable reduction of the (deutocerebral) primary olfactory pathway. We conclude that after the evolutionary transition from water to land, it is not trivial for arthropods to establish aerial olfaction. If we consider insects as an ingroup of Crustacea, then the Coenobitidae and Insecta may be seen as the most successful crustacean representatives in this respect.